(untitled) (Swiss Medical Weekly, 2021)
OBJECTIVE: This study aimed to assess the public perception of COVID-19 vaccination certificates as well as potential differences between individuals. METHODS: Between 17 March and 1 April 2021, a self-administered online questionnaire was proposed to all persons aged 18 years and older participating in the longitudinal follow-up of SARS-CoV-2 seroprevalence studies in Geneva, Switzerland. The questionnaire covered aspects of individual and collective benefits, and allowed participants to select contexts in which vaccination certificates should be presented. Results were presented as the proportion of persons agreeing or disagreeing with the implementation of vaccination certificates, selecting specific contexts where certificates should be presented, and agreeing or disagreeing with the potential risks related to certificates. Logistic regression was used to calculate odds ratios for factors associated with certificate non-acceptance. RESULTS: Overall, 4067 individuals completed the questionnaire (response rate 77.4%; mean age 53.3 ± standard deviation 14.4 years; 56.1% were women). About 61.0% of participants agreed or strongly agreed that a vaccination certificate was necessary in certain contexts and 21.6% believed there was no context where vaccination certificates should be presented. Contexts where a majority of participants perceived a vaccination certificate should be presented included jobs where others would be at risk of COVID-related complications (60.7%), jobs where employees would be at risk of getting infected (58.7%), or to be exempt from quarantine when travelling abroad (56.0%). Contexts where fewer individuals perceived the need for vaccination certificates to be presented were participation in large gatherings (36.9%), access to social venues (35.5%), or sharing the same workspace (21.5%). Younger age, no intent for vaccination, and not believing vaccination to be an important step in surmounting the pandemic were factors associated with certificate non-acceptance. CONCLUSION: This large population-based study showed that the general adult population in Geneva, Switzerland, agreed with the implementation of vaccination certificates in work-related and travel-related contexts. However, this solution was perceived as unnecessary for access to large gatherings or social venues, or to share the same workspace. Differences were seen with age, sex, education, socioeconomic status, and vaccination willingness and perception, highlighting the importance of taking personal and sociodemographic variation into consideration when predicting acceptance of such certificates.